Smart Attention (SAB-LSTM): A Revolutionary Model for Advanced Solar Energy Forecasting - Aljafari Belqasem; Babu Thanikanti Sudhakar (E3S Web of Conferences)
Solar power forecasting has a significant relevance to the optimization of energy management and to maintaining the reliability of the power systems against the growing use of renewable sources of energy globally. Accurate forecasting of solar energy generation would therefore allow for an increasingly effective integration of solar power into the grid, supporting the transition toward sustainable energy solutions. Most of the models suffer from the following crucial defects: weak representation of temporal dependency, failure to generalize on different weather conditions, and poor handling of nonlinear relationships in data. In this respect, this paper proposes a new Smart Attention Bi-LSTM model that integrates the strengths of the Bidirectional Long Short-Term Memory network with attention mechanisms. The SAB-LSTM model further improves performance in prediction by enabling the network to dynamically focus on the most valuable historical data points and hence overcome traditional methods of forecasting. This new method significantly improves the learning of complex patterns in the generation of solar energy and maintains high accuracy under variable seasonal conditions. The model was put to the most severe test with a rich dataset from Kaggle, including the various solar energy generation across different seasons. The contribution of this research covers not only the development methodologies like forecasting in the renewable energy sector but also sheds light on how deep learning techniques are important for robustness and accuracy in solar energy forecasts.